Implementation of Neighborhood Fund Policy in Community Empowerment Programs: A Case Study from Belimbing Village, Bontang City, Indonesia - Aziva Aulia Manggaramitha; Dea Rizky Amalia; Muhammad Aviv Adhitya Putra Pratama; Sry Reski Mulka (Golden Ratio of Community Services and Dedication, 2026)
This study examines the implementation of the Neighborhood Association (RT) fund policy in supporting community empowerment programs in RT 11, Belimbing Sub-district, BTN PKT Bontang Housing Complex. The government allocates Rp 50 million to each RT for empowerment activities; however, community participation in programs such as MSME training, urban farming, and supplementary feeding for toddlers remains relatively low. Participation typically ranges from 12–15 residents (60–75%) out of the 20-person quota, despite adequate funding. The objective of this study is to analyze factors influencing the implementation of the RT fund policy using George C. Edward III's policy implementation framework, which includes four variables: communication, resources, implementer disposition, and bureaucratic structure. This research employs a qualitative descriptive approach using purposive sampling. Twelve informants participated, including the Head of Belimbing Sub-district, the Head of RT 11, and eight community residents. Data were collected through in-depth interviews, participatory observation, and documentation. The findings show that communication functions effectively through formal meetings and WhatsApp groups. Resources are considered adequate, including financial support, facilities, and technical assistance, with funds distributed in the form of goods rather than cash. The disposition of implementers reflects a strong commitment, though some residents face limitations due to work schedules. The bureaucratic structure also operates regularly through community deliberation mechanisms. Overall, the implementation of the RT fund policy runs relatively well, supported by the four variables proposed by Edward III. Nevertheless, increasing community participation remains a challenge due to socioeconomic factors, particularly work commitments and time constraints. These findings suggest the importance of flexible program scheduling to accommodate working residents better and enhance participation in government-funded empowerment programs.